Cultivation Of Corn In The Dry Season Through Community Partnership Program In SMKN PP Kalasey - Pamandungan, Yefta; Wanget, Sesilia A.; Doodoh, Beatrix (Jurnal Agroekoteknologi Terapan, 2024)
The Community Partnership Program on Empowerment of SMKN PP Kalasey Students on Maize Cultivation in the Dry Season implemented in Kalasey Satu village, Mandolang District, Minahasa Regency, North Sulawesi, aims to: 1) Increase students' knowledge about corn cultivation in the dry season, 2) Increase students' knowledge about corn cultivation by modifying the planting rows between two varieties of corn, namely sweet corn and purple corn with a ratio of 4:1, 3) Empower educators at SMKN PP Kalasey as facilitators in corn cultivation activities in the dry season. This activity was carried out from September to October 2023 with the methods of agricultural extension, training, and plot demonstration and accompaniment. The program participants were students of SMKN PP Kalasey and were assisted by teachers as facilitators. Based on the results of the activity program, there is a positive impact on improving community values in terms of education in agriculture, increasing the application of science and technology regarding corn cultivation techniques in the dry season, increasing knowledge about corn cultivation techniques by modifying corn planting rows between sweet corn and purple corn to produce consumption materials, namely sweet purple corn, and knowledge about independent seed supply. Keywords: crop cultivation, maize, dry season Abstrak Program Kemitraan Masyarakat (PKM) mengenai Pemberdayaan Siswa SMKN PP Kalasey Mengenai Budidaya Tanaman Jagung Pada Musim Kemarau yang dilaksanakan di desa Kalasey Satu, Kecamatan Mandolang, Kabupaten Minahasa, Sulawesi Utara, bertujuan untuk: 1) Meningkatkan pengetahuan siswa mengenai budidaya tanaman jagung pada musim kemarau, 2) Meningkatkan pengetahuan siswa mengenai budidaya tanaman jagung dengan memodifikasi baris tanam antara dua varietas jagung yaitu jagung manis dan jagung ungu dengan ratio 4:1, 3) Memberdayakan tenaga pendidik (guru) di SMKN PP Kalasey sebagai fasilitator dalam kegiatan budidaya tanaman jagung di musim kemarau. Kegiatan PKM ini dilaksanakan pada September sampai dengan Oktober 2023 dengan metode Penyuluhan, Pelatihan dan Demonstrasi Plot serta Pendampingan. Peserta program PKM yaitu siswa SMKN PP Kalasey dan dibantu oleh para guru sebagai fasilitator. Berdasarkan hasil kegiatan PKM menunjukkan adanya dampak positif bagi perbaikan tata nilai masyarakat dalam hal pendidikan di bidang pertanian, peningkatan penerapan IPTEK mengenai teknik budidaya jagung dimusim kemarau, peningkatan pengetahuan mengenai teknik budidaya jagung dengan memodifikasi baris tanam jagung antara jagung manis dan jagung ungu dalam upaya menghasilkan bahan konsumsi berupa jagung manis berbulir ungu, serta pengetahuan mengenai penyediaan benih secara mandiri. Kata kunci: budidaya tanaman, jagung, kemarau